Rešeto za iskanje praštevilskih dvojčkov - Lampret, Srečko (Obzornik za matematiko in fiziko, 2013)
In this paper a new characterization of twin prime pairs is obtained. This result gives us an elementary method for finding twin prime pairs up to a given integer.
Keywords: numerical analysis; teorija števil; praštevila; prime numbers; prime pairs; praštevilski dvojčki